Influência da música, da iluminação e Crowding na atenção do consumidor: um estudo exploratório em ambiente de laboratório de Varejo - Securato, Andrea Silvia (2017)
The store environmental factors and their influences on consumption are current and relevant themes, dealt with by much of the academic literature. These factors, divided into auditory, visual, olfactory, tactile, tasteful and social, are presented as the focus of managerial strategies, do to the interferences in the dynamics of attention at the point of sale. This paper seeks to clarify this dynamic, in face of three factors: auditory, visual and social. For that, the variables of music, lighting and crowding and their influences on consumer attention in a simulated supermarket environment were considered. The analysis was carried out in the Retail Lab of the School of Advertising and Marketing with the use of EyeTracking technology to identify the visual attention in front of six varied scenarios. The results point to a positive impact of music of moderate height (ambient sound), as well as influences of the high and natural lighting and acceleration of the decisions of purchase by the density of individuals (crowding). Such results contribute to the academic and managerial knowledge in marketing, with indication of proposals for future studies.